PROBLEM-BASED LEARNING IN PRIMARY SCHOOLS: ENHANCING CONCEPTUAL UNDERSTANDING AND PROBLEM-SOLVING SKILLS - Rofiqoh Hasan Harahap; Hale Y?lmaz; Aylin Erdo?an (International Journal of Educatio Elementaria and Psychologia, 2026)
Problem-Based Learning has received increasing attention as an instructional approach capable of fostering higher-order thinking, meaningful knowledge construction, and learner autonomy within primary education. Persistent reliance on teacher-centered instruction continues to limit students’ opportunities to develop conceptual understanding and apply knowledge to authentic problem situations. This study aimed to examine the effectiveness of Problem-Based Learning in enhancing conceptual understanding and problem-solving skills among primary school students. A mixed-methods sequential explanatory design was employed involving 920 students from twelve elementary schools. Quantitative data were collected using validated assessments of conceptual understanding, problem-solving skills, critical thinking, cognitive engagement, collaborative learning, self-regulated learning, and academic achievement, and analyzed through repeated-measures analysis of variance, generalized linear mixed-effects modeling, structural equation modeling, mediation analysis, and hierarchical regression. Qualitative evidence was obtained through interviews, classroom observations, teacher reflective journals, and instructional document analysis, followed by thematic interpretation. Findings revealed significant improvements in conceptual understanding, problem-solving performance, critical thinking, collaborative learning, cognitive engagement, and academic achievement among students participating in Problem-Based Learning. Conceptual understanding emerged as the strongest predictor of problem-solving ability, while teacher scaffolding and self-regulated learning significantly strengthened inquiry processes and sustained learning outcomes. Results indicate that effective Problem-Based Learning depends on the integration of authentic problem scenarios, collaborative inquiry, structured teacher guidance, reflective learning, and supportive classroom environments. The proposed instructional framework offers practical guidance for improving meaningful learning and higher-order thinking in primary education.